Dynamics of Epstein–Barr virus on post‐transplant lymphoproliferative disorders after antithymocyte globulin‐conditioned allogeneic hematopoietic cell transplant. Issue 5 (12th September 2021) - Lindsay, Julian; Othman, Jad; Yong, Michelle K.; Ritchie, David; Chee, Lynette; Tay, KimHeng; Tio, Shio Yen; Kerridge, Ian; Fay, Keith; Stevenson, William; Arthur, Chris; Chen, Sharon C.‐A.; et al.
Abstract: Background: The use of antithymocyte globulin (ATG) in allogeneic hematopoietic cell transplant (HCT) is associated with an increased risk of Epstein–Barr virus (EBV) reactivation and post‐transplant lymphoproliferative disorders (PTLD). The dynamics and outcomes of EBV‐DNAemia are not well described in this population. Methods: We retrospectively assessed the kinetics of EBV‐DNAemia after ATG conditioning of HCT recipients. Receiver operating characteristic (ROC) curves were used to assess EBV‐DNAemia to predict EBV‐PTLD in this group. Results: A total of 174/405 (43%) consecutive HCT recipients from two centers met inclusion criteria of ATG conditioned, non‐B‐cell lymphoma patients. Of these with EBV‐DNA measured using standardized IU/ml, 78.6% (92/117) developed EBV‐DNAemia: 62% spontaneously resolved; 19% cleared after preemptive rituximab, and 13% developed EBV‐PTLD. ROC curve analysis using maximum pre‐EBV‐PTLD EBV‐DNAemia, demonstrated an AUC of 0.912 with EBV‐DNAemia of 9782 IU/ml, associated with 82.6% sensitivity and 94.4% specificity for development of EBV‐PTLD. Median time for EBV‐DNAemia to increase from initial detection to >1000 IU/ml was 7 days; to >10 000 IU/ml, 12 days; and to >100 000 IU/ml, 18 days. Median EBV‐DNAemia level prior to administration of rituximab was significantly lower in patients with successful preemptive treatment, compared with those who developed EBV‐PTLD (3.41 log10 IU/ml [3.30–3.67] vs. 4.34 log10 IU/ml [3.85–5.13], p = .002; i.e., 2628 IU/ml vs. 21 965 IU/ml, respectively). Conclusions: EBV‐DNAemia >10 000 IU/ml was the strongest predictor of the development of EBV‐PTLD, and progression to this level was rapid in ATG‐conditioned HCT recipients. This information may guide EBV‐PTLD management strategies in these high‐risk patients.